Structural properties, photoelectric and photoluminescent characteristics of nanostructured silicon - Luchenko, A.I.; Melnichenko, M.M.; Svezhentsova, K.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2012)
. Nanostructured silicon layers (3–60 nm) have been formed upon substrates of monocrystalline silicon with a very large area (100 cm2 ), multicrystalline and metallurgical silicon by stain etching. We studied optical and structural properties of nanostructured silicon using scanning tunnel microscopy, scanning electron microscopy, Auger electron spectroscopy, secondary ion mass spectrometry, and photoluminescence methods. Results of studying the nanostructured Si properties obtained using the method of chemical processing have confirmed an opportunity to create this multifunctional material with stable characteristics. The authors have developed the sensor systems with use of nanostructured silicon as a sensitive layer, which properties depend on thickness of the obtained layer and are controlled by parameters of the respective technological process. Using the example of the photoluminescent sensor with the nanostructured Si layer, it has been shown that such a sensor can be successfully used to detect small concentrations of toxins (pesticides phosalone 10⁻⁸ - 10⁻⁹ mol/l ) as well as for specific biological pollutants, such as protein components, polysaccharides, cells worsening the quality of products of biotechnological synthesis.